Noble Gas Release from Bedded Rock Salt during Deformation. (20th June 2019) - Bauer, Stephen J.; Gardner, W. Payton; Lee, Hyunwoo
Abstract : Geogenic noble gases are contained in crustal rocks at inter- and intracrystalline sites. In this study, bedded rock salt from southern New Mexico was deformed in a variety of triaxial compression states while measuring the release of naturally contained helium and argon utilizing mass spectrometry. Noble gas release is empirically correlated to volumetric strain and acoustic emissions. At low confining pressures, rock salt deforms primarily by microfracturing, rupturing crystal grains, and releasing helium and argon with a large amount of acoustic emissions, both measured real-time. At higher confining pressure, microfracturing is reduced and the rock salt is presumed to deform more by intracrystalline flow, releasing less amounts of noble gases with fewer acoustic emissions. Our work implies that geogenic gas release during deformation may provide an additional signal which contains information on the type and amount of deformation occurring in a variety of earth systems.